Bunga Bank dalam Hukum Islam; Komparasi Pemikiran Imam Ali Jum'ah dan Imam Jadul Haq Ali - Abdillah, Muhammad Alwin; Awwaluzzikri; Muhammaddiah, Muhammad Rusdi bin (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2024)
This study aims to analyze the views of these two prominent scholars on bank interest and to explore their perspectives on applying Sharia principles in modern financial systems. This article employs a descriptive-analytical approach using literature-based research, drawing on scholarly articles about bank interest and the two scholars. Sheikh Ali Jum'ah perceives bank interest as permissible if it aligns with the maqasid al-Shariah, promotes public benefit, and does not violate definitive texts (nass qat'i), thereby enabling the integration of Sharia principles into modern financial systems. Conversely, Sheikh Jadul Haq Ali asserts that bank interest is classified as riba qardh, strictly prohibited by Sharia, underscoring the importance of preserving the purity of Islamic law and encouraging Muslims to avoid interest-based transactions to ensure the blessings of wealth.